HUBUNGAN POLA ASUH ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA - Nur Syawalia Fitri; Siti Masyithoh (LP2M IAI Muhammadiyah Bima, 2023)
The reason for this research is to; (1). Knowing the causes of decreased student motivation; (2). Knowing the implications of parenting patterns on students' learning motivation, and (3). Analyzing the urgency of parenting parents to student learning motivation. This study uses qualitative methods and descriptive analysis research types. Sources of data were obtained from literature studies by citing theories from various scientific journals, printed books, and e-books. Research Results Show (1). Parenting style is divided into three; authoritarian, permissive, authoritative (2). The application of each parenting pattern has a positive and negative impact on student learning motivation (3). Student motivation is further increased in the application of authoritative parenting